CTA Annual Report 2006 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
The main challenge for CTA is to keep pace with the rapidly changing environment in which we work... Dr Hansjörg Neun, Director, CTA